(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
The objective of this study was to assess the concentrations of Zn, Fe, Se, and Ni micronutrients present in some commonly consumed herbal snuffs in Sokoto, Nigeria using atomic absorption spectroscopy. The concentrations of zinc and iron metals present in brands of herbal snuff in Sokoto Nigeria reveal, the zinc concentration ranges from 0.12 ± 0.02 (recorded in DR Lambo special Sundu) to 0.33 ± 0.002 ppm (Hajiya Ayisha Snuff AK47 Blue cover), and iron ranges from 0.97 ± 0.6 (found in DR Lambo special Sundu) to 8.92 ± 0.2 ppm (AK 47). The concentrations of selenium and nickel metals in some selected snuff materials consumed in Sokoto, Nigeria reveal, the selenium concentration ranges from 0.05 ± 0.002 (Hajiya Ayisha snuff AK 47 green cover) to 0.12 ± 0.001 (revealed in Dr Lambo Herbal Powder) ppm. Nickel ranges from 0.02 ± 0.001 to 0.04 ± 0.002 ppm. All the determined elements are within safe levels when compared to World Health Organization (WHO) permissible limits and are probably safe for human consumption.